Adaptation strategies to climate change and their impact on agricultural production in Punjab, Pakistan - Mustafa, Ghulam (2017)
Climate change (increase temperature and erratic rainfall patterns) has brought about possibly permanent alterations to our planet's ecological, biological and geological systems. One way to handle climatic variations is the adaptation to climate change. Studies have found that adverse impacts of climatic adversaries can easily be muted by adaptation to climate change. But, how effective adaptation strategies in response to climate change vulnerabilities are is a crucial question confronting farmers across the world especially in developing countries. Whereas literature has found the effectiveness of adaptation strategies based on perceptions of farmers but one cannot generalize this method as the perceptions vary from region to region and even from person to person. This study ranked the adaptation techniques based on actual efficiency of each adoption measure. There are different socio economic, demographic and institutional factors that affect farmers’ awareness of and adaptation strategies to climate change that further need to be explored. The study in hand found these determinants in Pakistan’s context.